2007
DOI: 10.2109/jcersj.115.354
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Ag+/Na+ Ion-exchanged Aluminosilicate Glasses

Abstract: Mechanical properties of Ag Na ion-exchanged aluminosilicate glasses are investigated. The aluminosilicate glass samples with the thickness of 1 mm and homogeneous Ag Na concentrations were prepared via the ion exchange in the molten salt at 450? C and the following post-heating in the ambient atmosphere. Measured Young's modulus, Vickers hardness and fracture toughness in a dry nitrogen atmosphere change nonlinearly with increasing Ag Ag Na ratio, and show the maximum values, 75 GPa, 560 kgmm 2 and 0.84 MNm 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The mechanical properties of silver/sodium ion-exchanged aluminosilicate glass, which has no nonbridging oxygen, have been intensively studied by Funabiki et al 12) They showed that the (yield stress)/(Young's modulus) representing the minimum strain of the glass network to be broken was monotonically decreased with the replacement of sodium by silver ions. They have discussed the relationship between the mechanical properties and the structural aspect of the glass in detail and considered that the low coordination number of silver ions in the glass is one of the origins of the mechanical behaviors of the ion-exchanged glass.…”
Section: Molding Testmentioning
confidence: 99%
“…The mechanical properties of silver/sodium ion-exchanged aluminosilicate glass, which has no nonbridging oxygen, have been intensively studied by Funabiki et al 12) They showed that the (yield stress)/(Young's modulus) representing the minimum strain of the glass network to be broken was monotonically decreased with the replacement of sodium by silver ions. They have discussed the relationship between the mechanical properties and the structural aspect of the glass in detail and considered that the low coordination number of silver ions in the glass is one of the origins of the mechanical behaviors of the ion-exchanged glass.…”
Section: Molding Testmentioning
confidence: 99%